Application the Project Based Learning Model with Picture Media to Improve the Poetry Writing Skills of Elementary Students - Neny Eka Yulia Pasatria; Supri Wahyudi Utomo; Endang Sri Maruti (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
(1) research purposes: developing innovative learning methods to improve students’ competence in writing poetry. Through this research, it is hoped that the results can contribute to the development of learning methods in elementary schools, especially in Indonesian language learning. In addition, this research is also expected to provide new insights for teachers in applying the Project Based Learning model to create, (2) research methods: The type of research used was Classroom Action Research. The subjects were 11 fourth-grade students of SDN Bakalan II Tambakrejo. This research was planned for two cycles. If the first cycle did not meet the success indicators, it would proceed to the second cycle, and (3) research results: Student activity in the application of the Problem Based Learning learning model for the material of writing poetry experienced an increase in cycle I. Student activity in the material of writing poetry was included in the category quite good , with an average result of 78, cycle II student activities in the poetry writing material are included in the category good , with the average result obtained by students being 84. Teacher Activities in Implementing the Problem Based Learning Model The poetry writing material in cycle I is included in the good category. This is based on the average results obtained, namely 8.5. In cycle II, teacher activities in writing poetry are included in the very good category. This is based on the average results obtained, namely 9.4. Student Learning Outcomes on the Implementation of Problem Based Learning In the Poetry Writing material, in cycle I, the average overall student score was 74.09, which falls into the sufficient category according to the score conversion guidelines. Meanwhile, student completion reached 100%, with all students achieving scores above the minimum criteria. Cycle II showed an overall average student score of 85.5, which falls into the good category according to the grade conversion guidelines. Meanwhile, student completion reached 100%, with all students achieving scores above the minimum criteria.